Spasticity in disorders of consciousness: a behavioral study - Thibaut, F A; Chatelle, C; Wannez, S; Deltombe, T; Stender, J; Schnakers, C; Laureys, S; Gosseries, O (European journal of physical and rehabilitation medicine, 2015)
Spasticity is a frequent complication after severe brain injury, which may impede the rehabilitation process and diminish the patients' quality of life. We here investigate the presence of spasticity in a population of non-communicative patients with disorders of consciousness. We also evaluate the correlation between spasticity and potential factors of co-morbidity, frequency of physical therapy, time since insult, presence of pain, presence of tendon retraction, etiology and diagnosis. Cross-sectional study. University Hospital of Liège, Belgium. Sixty-five patients with chronic (>3 months post insult) disorders of consciousness were included (22 women; mean age: 44±14 y; 40 with traumatic etiology; 40 in a minimally conscious state; time since insult: 39±37 months). Spasticity was measured with the Modified Ashworth Scale (MAS) and pain was assessed using the Nociception Coma Scale-Revised (NCS-R). Out of 65 patients, 58 demonstrated signs of spasticity (89%; MAS≥1), including 40 who showed severe spasticity (61.5%; MAS≥3). Patients with spasticity receiving anti-spastic medication were more spastic than unmedicated patients. A negative correlation was observed between the severity of spasticity and the frequency of physical therapy. MAS scores correlated positively with time since injury and NCS-R scores. We did not observe a difference of spasticity between the diagnoses. A large proportion of patients with disorders of consciousness develop severe spasticity, possibly affecting their functional recovery and their quality of life. The observed correlation between degrees of spasticity and pain scores highlights the importance of pain management in these patients with altered states of consciousness. Finally, the relationship between spasticity and treatment (i.e., pharmacological and physical therapy) should be further investigated in order to improve clinical care. Managing spasticity at first signs could improve rehabilitation of patients with disorders of consciousness and maximize their chances of recovery. In addition, decreasing this trouble could allow a better quality of life for these non-communicative patients.